Determining the reliability and usability of change of direction speed tests in adolescent female soccer players: a systematic review - Pardos-Mainer, E.; Casajús, J. A.; Julián, C.; Bishop, C.; Gonzalo-Skok, O. (The Journal of Sports Medicine and Physical Fitness, 2020)
INTRODUCTION: This review aimed 1) to describe the most common tests used for assessing change of direction (COD) performance; 2) to detail the reliability of current COD tests; 3) to provide an overview of current intervention strategies used to improve COD performance in adolescent female soccer players. EVIDENCE ACQUISITION: A computerized search was conducted in the PubMed, Cochrane Plus and Web of Science (from 1995 to January 2020) for English and Spanish language and peer-reviewed investigations. EVIDENCE SYNTHESIS: A total of 221 studies were identified, with only 16 meeting the specific search criteria. The main findings were that eleven different tests have been used to assess COD performance with intraclass correlation coefficient and coefficient of variation values between 0.72-0.99 and 1-10.6%, respectively. The number of CODs performed during each test ranged from 1 to 9 within a range of 45º to 180º and with a duration <5 s, 5-9 s and >10 s. CONCLUSIONS: Findings indicate that the reliability of the COD tests seems to depend on: the equipment used, the surface tested on and the technical level of the soccer player. These results should be interpreted with caution as they may be influenced by the period of growth and maturation, the playing position of the player and the period of the soccer season. Finally, strength and power drills could be considered as appropriate to improve COD performance.